Solving the puzzle of neurological diseases: an interview with Huda Zoghbi - Huda Y. Zoghbi (The Company of Biologists, 2017)
Huda Zoghbi's achievements in the field of neurology are internationally acclaimed. She is best known for elucidating the genetic basis of two complex neurological disorders, spinocerebellar ataxia type 1 and Rett syndrome, and has been honored with many prizes, including The Shaw Prize in Life Science and Medicine in 2016 and the 2017 Breakthrough Prize for Life Sciences. A diligent and creative research scientist at the bench, a respected lab mentor and founding Director of the Jan and Dan Duncan Neurological Research Institute at Texas Children's Hospital, her inspiration has always been the burning need to help patients faced with devastating neurological problems. Her pursuit of the mechanisms mediating spinocerebellar ataxia and Rett syndrome has been dogged, requiring 30 years of focused effort. As highlighted in this interview, her work is now paying dividends by starting to reveal potential therapeutic targets for these intractable and complex disorders.